PERANAN ANGGARAN PIUTANG DALAM MENINGKATKAN EFEKTIVITAS PENGELOLAAN PIUTANG USAHA BAGI UMKM: TINJAUAN LITERATUR - Awie Alpany Br Sitorus; Neng Risya; Dini Vientiany (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the role of accounts receivable budgeting in improving the effectiveness of accounts receivable management in Micro, Small, and Medium Enterprises (MSMEs). MSMEs commonly apply credit sales as a strategy to increase revenue; however, this practice also creates risks of uncollectible receivables that may disrupt cash flow and threaten business sustainability if not properly managed. This research adopts a qualitative approach using a literature review method, drawing on relevant national and international journal articles published within the last five years. The data were analyzed using descriptive qualitative techniques through classification, comparison, and synthesis of previous research findings. The results indicate that accounts receivable budgeting plays a crucial role as both a planning and control tool in MSME receivable management. The implementation of receivable budgets enables MSMEs to forecast cash inflows, control problematic receivables, increase receivable turnover, and improve cash flow stability. Furthermore, receivable budgeting supports greater financial discipline and facilitates structured evaluation of credit policies. Therefore, accounts receivable budgeting can be considered a strategic, simple, and practical financial management instrument to enhance the effectiveness of receivable management and support the long-term sustainability of MSMEs.